2008
DOI: 10.1109/jsac.2008.080913
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Anarchy in Overlapping Wireless Networks

Abstract: We investigate the behavior of a large number of selfish users that are able to switch dynamically between multiple wireless access-points (possibly belonging to different standards) by introducing an iterated non-cooperative game. Users start out completely uneducated and naïve but, by using a fixed set of strategies to process a broadcasted training signal, they quickly evolve and converge to an evolutionarily stable equilibrium. Then, in order to measure efficiency in this steady state, we adapt the notion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Up to the knowledge of the authors, the state of art of the BS sharing and BS selection scenarios is described by the following contributions: [10], [4], [5], [8]. In [10], the BS selection problem is investigated by considering that each node is characterized by a fixed single user spectral efficiency. Here, the authors showed that based on the scheme of exponential learning, players converge to an evolutionarily stable equilibrium.…”
mentioning
confidence: 99%
“…Up to the knowledge of the authors, the state of art of the BS sharing and BS selection scenarios is described by the following contributions: [10], [4], [5], [8]. In [10], the BS selection problem is investigated by considering that each node is characterized by a fixed single user spectral efficiency. Here, the authors showed that based on the scheme of exponential learning, players converge to an evolutionarily stable equilibrium.…”
mentioning
confidence: 99%
“…x is decreasing for x > 1 + γ * that there is always only one such y. 31 To prove part 2) first note that the maximum utility that can be obtained in this game is bounded…”
Section: F Proof Of Propositionmentioning
confidence: 97%
“…The channel state of knowledge window or the stationary time of the environment needs to be at least greater than the convergence time of the algorithms. Due to the very complex nature of the problem, new tools and a thinking of new sort need to be developed taking into account evolution and learning aspects [41]- [42].Moreover, instead of looking at how equilibria (which in any case will happen only for a short period of time) can be maintained, one should better focus on tools to understand how new equilibria states emerge from nonequilibrium situations.…”
Section: Iv-f the Dynamics Foundationsmentioning
confidence: 99%